THE EFFECT OF ADDITIONAL ARABICA GROUND COFFEE ON THE FERMENTATION PROCESS ON ORGANOLEPTIC QUALITY OF COW’S MILK KEFIR - H., MUTTAQIN; LINDAWATI, S. A.; MIWADA, I N. S. (Majalah Ilmiah Peternakan, 2022)
This study aims to determine the effect of adding arabica ground coffee to the fermentation process on the orga- noleptic quality of cow’s milk kefir. The experimental design used was a completely randomized design (CRD) with five treatments and three replications, namely kefir with the addition of 0% arabica ground coffee (P0), kefir with the addition of 1% arabica ground coffee (P1), kefir with the addition of 2% arabica ground coffee. (P2), kefir with the addition of 3% arabica ground coffee (P3) and kefir with the addition of 4% arabica ground coffee (P4). The va- riables observed include color, aroma, taste, texture and overall acceptance. Analysis on color, aroma and taste sho- wed significantly different results (P <0.05) with a numerical scale of 3-4.72 respectively from white to light brown, 2.76-4.88 from sour to coffee flavored and 2.76-4.68 from very sour to bitter acid. Analysis on texture showed that P0 and P1 were not significantly different (P> 0.05) but P2, P3 and P4 were significantly different (P <0.05) from P0 with a numerical scale of 3-3.52 from ordinary to slightly soft. The analysis of the level of liking on the overall acceptance shows that P0, P1 and P2 are not significantly different (P>0,05), but P3 and P4 are significantly diffe- rent (P<0,05) with a numerical scale of 3.08-4.36 from ordinary to like. Based on the results of this study, it can be concluded that the addition of 4% Arabica ground coffee is the most preferred by the panelists.